Nothing in Biology Makes Sense Except in Light of Its “Proper” Epistemic Framework - Kilian, Krzysztof (Filozoficzne Aspekty Genezy, 2025)
Dobzhansky argues in a specific way in favour of the theory of evolution, using an argumentative scheme that, in his view, allows one to demonstrate the superiority of naturalistic explanations over anti-naturalistic ones. However, using such a research tool as epistemic frameworks it is relatively easy to show that the same scheme can be employed to demonstrate the superiority of anti-naturalistic explanations over naturalistic ones.